Sequence Indicators of Junior High School Students’ Mathematical Imagination Abilities - Novi Andri Nurcahyono; Didi Suryadi; Sufyani Prabawanto; Eka Novarina (Peneliti.net, 2020)
Each student has a different level of mathematical imagination ability. To find out the level of mathematical imagination ability, it is first necessary to arrange indicators of mathematical imagination ability based on the sequence of appearance from the earliest. The participants of this study were 20 8th grade students consisting of 13 female students and 7 male students. This research is a descriptive qualitative research. Assist instruments in this study consisted of written tests in the form of essays, interview guidelines, and observation sheets. Data analysis was performed by data reduction, data display, and conclusion drawing. The results obtained from this study are sequence indicators of junior high school students' mathematical imagination abilities namely, sensibility, intuition, crystallization, transformation, exploration, elaboration, productivity, effectiveness, novelty.